Mixed mammary carcinoma in a guinea pig (Cavia porcellus) - Martinez-Pereira, Malcon; Alcântara Gomes, Paulo Henrique; Pereira, Lucas de Paula; Berri, Alessandra Nelcir; Padilha, Vanessa Sasso; Veiga, Angela Patricia Medeiros; Baron, Aline Ruediger; Ramos, Adriano Tony (Acta Scientiae Veterinariae, 2023)
Background: Thirteen mammary neoplasms types are described in Cavia porcellus in the literature. Among these, the most prevalent are the benign and spontaneous neoplasms (70%), between the malignant stand out the adenocarcinomas (majoritary), tubular and tubulopapillary, however, when it comes to mixed carcinomas, despite being rare, they present greater malignancy. The present study aims to report the case of a guinea pig cytologic and histologically diagnosed with mammary gland mixed carcinoma treated by surgical excision. Case: A 1-year-old female Abyssinian guinea pig weighing 1.1 kg was treated at the Wild and Exotic Animal Sector of the Federal University of Santa Catarina (UFSC)in the city of Curitibanos, SC, Brazil. The patient revealed an alert and docile temperament without considerable physiological changes in the physical examination. The patient presented a mass, measuring 1.4 x 1.6 cm with a nodular appearance, firm consistency and not adhered in the region of the left inguinal mammary gland. A sample was collected by fine needle aspiration biopsy technique (FNAB), which revealed to be suggestive of malignant neoplasm from epithelial tissue, due observation of presence of 3-dimensional clusters of epithelial cells, with discrete anisocytosis and anisokaryosis. In 7 days, the nodule showed gradual and progressive growth, measuring 2.0 x 1.6 cm. Radiographs were taken in order to rule out the presence of metastases in other organs and systems. The suitable treatment was surgical excision of the nodule and mammary gland, which occurred without intercurrences, and the material was sent for histopathological analysis. On the day of the surgical procedure, the nodule measured 2.4 x 1.6 cm. As a result, it was noted the rupture of tubules, isolated cells or forming nests in the middle of the stroma composed mainly of myoepithelial cells and adipocytes and presence of lymphoplasmacytic and neutrophilic infiltrate, compatible with mixed mammary gland carcinoma in a grade I. After 10 days of the procedure, the patient was released healthy and weighing 1.18 kg. Due to the absence of metastasis was not indicated post-surgical chemotherapy, however it was proposed ovariohysterectomy in order to prevent recurrence. So far, there has been no sign of recurrence or development of metastases in the patient. Discussion: In fact, guinea pig mammary neoplasms are locally invasive, large in size and highly vascularized, but they rarely metastasize, and there is no sexual predisposition. An important characteristic of the guinea pigs neoplasms is the fast growth that can be associated with the accelerated metabolism in these animals. Diagnostic methods such as FNAB are important to differentiate non-neoplastic from neoplastic processes, as mastitis or mammary hyperplasia. However, the cytologic appearance may vary greatly depending on the type of neoplasm, thus the histopathology provides the definitive diagnosis. Surgical excision is the treatment of choice, once these animals are poorly tolerant to chemotherapy. The adoption of measures, as ovariohysterectomy, can help the treatment or prevention of mammary neoplasms, although the tutor refutes the indication in this case. On the other hand, there is a still gap in the knowledge of neoplasms in guinea pig, making studies allow us to understand the pathophysiology of these diseases in this specie. Keywords: mammary carcinoma, mammary gland, neoplasm, guinea pig. Título: Carcinoma mamário misto em porquinho-da-Índia (Cavia porcellus) Descritores: carcinoma mamário, glândula mamária, neoplasia, porquinho-da-índia.